Patient experiences of living with cancer before interaction with palliative care services in Zimbabwe: A qualitative secondary data analysis. (17th June 2022) - Dandadzi, Adlight; Chapman, Emma; Chirenje, Z. Mike; Namukwaya, Elizabeth; Pini, Simon; Nkhoma, Kennedy; Allsop, Matthew J.
Abstract: Objective: Cancer patients in Zimbabwe typically access health services with advanced disease, limiting treatment choices and lessening the likelihood of positive treatment outcomes. We outline experiences of patients with advanced cancer prior to interaction with palliative care services to identify targets for future intervention development to enhance care delivery in Zimbabwe. Methods: Participants were purposively sampled adult patients with advanced cancer. We adopted a thematic approach to guide a qualitative secondary data analysis exploring factors influencing support sought by participants, external factors influencing decision making across the disease trajectory and the process for seeking and accessing palliative care. Results: Participants reported fragmented and uncoordinated care, from initial symptom experience and throughout disease progression. A recurring notion of disjuncture was present through participants' experiences of gaps, breaks and discontinuity across the disease trajectory. Each step had a beginning and end without clear routes for transition with movement between steps as a result of happenstance or informal encounters. Conclusion: Targets for intervention development at the patient and family level exist that may reduce the disjuncture currently experienced between need and care provision. A holistic response that incorporates engagement with policy actors is critical to addressing prominent financial constraints for patients.